Objective crop protection: entomology, plant pathology and nematology for ARS Prelims - Prasad, T.V.; Srinivas, P. (New Delhi : New Vishal Publications, 2012)
Crop protection which includes entomology, plant pathology and nematology is one of the prominent branches of agriculture which deals with the saf guarding of plants from various biotic stresses. Due to enormous breadth and diversity of the subject, a number of books have been written on various basic, fundamental, general and applied aspects.
Keywords: Crop-protection